Menganyam Pelangi Inklusi: Dinamika Implementasi Pendidikan Inklusi di SD Budi Mulia Sandika Jakarta - Julisesko Buaton; Lisa G Kailola; Bintang R Simbolon (LPPM Institut Pendidikan Nusantara Global, 2026)
This study explores the implementation of inclusive education at Budi Mulia Sandika Primary School, Jakarta, highlighting supporting and inhibiting factors, strategies for raising public awareness, and its impact on student development. Qualitative research was conducted through structured interviews and unstructured observations of 21 participants (teachers, principals, parents, regular students, and students with special needs) during September–October 2025. The results show that the principal's transformative leadership, a caring school culture, and teacher enthusiasm support inclusion, while the lack of teacher training, limited facilities, low parental support, high number of students per class, and social stigma are obstacles. Inclusion improves students' social interaction and empathy, but the academic achievement of students with special needs remains stagnant. This study emphasises the need for continuous teacher training, flexible curricula, educational technology, disability-friendly infrastructure, parental and community involvement, effective public communication, and data-based monitoring and evaluation systems.